Aktivitas Bauran Komunikasi Pemasaran Di Perusahaan Jamu Ibu Tjipto Kota Tegal - Susanto, Agus; Sunardi, Ahmad (Program Studi Ilmu Komunikasi Universitas Muhammadiyah Yogyakarta, 2017)
Activities marketing today not just activities selling, but is activity to gain loyal customers. This is not easy work so there needs integrated marketing communications. The example of integrated marketing communications implementation is by use marketing communications mix, which divided in advertising activity, sales promotions, special event & experiences, public relations & publicity, direct marketing and personal selling.The problems in research discussed by descriptive qualitative approach. This study attempts to give a description of about their activities of marketing communications mix by Perusahaan Jamu Ibu Tjipto Tegal City to get drug market share in Tega City. Data collection is done by using in-depth interviews with two key participants and field observation with compiles literature that supports. Through this research obtained a description of marketing communications mix activities in Perusahaan Jamu Ibu Tjipto, which marketing activity not arrayed integrally and adjust human resources and their funds are. The marketing communications mix not carried out very maximum shown to be just advertising, sales promotions , direct marketing and personal selling done. Keywords : marketing mix, marketing communication mix, herbal company